Integrative pan-cancer landscape of MMS22L and its potential role in hepatocellular carcinoma - Guo, Zhiting; Liu, Fahui; Gong, Qiming (Frontiers in Genetics, 2022)
Methyl methanesulfonate-sensitivity protein 22-like (MMS22L) is crucial in protecting genome integrity during DNA replication by preventing DNA damage and maintaining efficient homologous recombination. However, the role of MMS22L in human cancers remains unclear. Here, we reported the landscape of MMS22L using multi-omics data and identified the relationship between the MMS22L status and pan-cancer prognosis. In addition, the correlation of MMS22L mRNA expression levels with tumor mutational burden, microsatellite instability, homologous recombination deficiency, and loss of heterozygosity in pan-cancer was also described in this study. Furthermore, this study was the first to characterize the relationship between mRNA expression of MMS22L and immune cell infiltration in the tumor microenvironment in human cancer. Concurrently, this study explored the crucial role of MMS22L in different immunotherapy cohorts through current immunotherapy experiments. Eventually, we investigated the role of MMS22L in hepatocellular carcinoma (HCC). The results demonstrated that MMS22L is widely expressed in multiple HCC cell lines, and our results emphasized that MMS22L was involved in HCC progression and affects the prognosis of patients with HCC through multiple independent validation cohorts. Collectively, our findings reveal the essential role of MMS22L as a tumor-regulating gene in human cancers while further emphasizing its feasibility as a novel molecular marker in HCC. These findings provide an essential reference for the study of MMS22L in tumors.